Benzoyl isothiocyanate modified surface of silica gel as the extraction material for adsorbing steroid hormones in water. Issue 9 (20th February 2023) - Li, Qiang; Zhao, Jia-Hui; Lai, Hua-Jie; Liu, Bo; Zhang, Miao; Xiao, Ning-Lan; Wang, Hao-Dong; Jin, Tao
Abstract : Steroid hormones have been listed as priority pollutants in the environment, and their detection and pollution control deserve our extensive attention. Abstract : Steroid hormones have been listed as priority pollutants in the environment, and their detection and pollution control deserve our extensive attention. In this study, a modified silica gel adsorbent material was synthesized by benzoyl isothiocyanate reaction with hydroxyl groups on the silica gel surface. The modified silica gel was used as a solid phase extraction filler for the extraction of steroid hormones from water, which was further analyzed by the HPLC-MS/MS method. The FT-IR, TGA, XPS, and SEM analysis indicated that benzoyl isothiocyanate was successfully grafted on the surface of silica gel to form a bond with an isothioamide group and benzene ring as the tail chain. The modified silica gel synthesized at 40 °C showed excellent adsorption and recovery rates for three steroid hormones in water. Methanol at pH 9.0 was selected as the optimal eluent. The adsorption capacity of the modified silica gel for epiandrosterone, progesterone, and megestrol acetate was 6822 ng mg −1, 13 899 ng mg −1, and 14 301 ng mg −1, respectively. Under optimal conditions, the limit of detection (LOD) and limit of quantification (LOQ) for 3 steroid hormones by modified silica gel extraction with HPLC-MS/MS detection were 0.02–0.88 μg L −1 and 0.06–2.22 μg L −1, respectively. The recovery rate of epiandrosterone, progesterone, and megestrol was between 53.7% and 82.9%, respectively. The modified silica gel has been successfully used to analyze steroid hormones in wastewater and surface water.